Obesity- and aging-induced excess of central transforming growth factor-β potentiates diabetic development via an RNA stress response - Yan, Jingqi (2014)
The brain, in particular the hypothalamus, plays a role in regulating glucose homeostasis; however, it remains unclear if the brain is causally involved in diabetic development. Here, we identified that hypothalamic TGF-β is excessive under conditions of not only obesity but aging, which are two general etiological factors of diabetes. Pharmacological and genetic approaches consistently revealed that brain TGF-β excess caused hyperglycemia and glucose intolerance in a body weight-independent manner. Cell-specific genetic models demonstrated that astrocytes are responsible for brain TGF-β excess, and POMC neurons are crucial for the pro-diabetic effect of TGF-β excess. Mechanistically, TGF-β excess induced hypothalamic RNA stress response to accelerate IκBα mRNA decay, leading to an atypical, mRNA metabolism-driven hypothalamic NF-κB activation which links obesity as well as aging to hypothalamic inflammation. In conclusion, brain TGF-β excess and induction of RNA stress response and hypothalamic inflammation are important for the pro-diabetic effects of obesity or aging.